2009
DOI: 10.1055/s-0029-1216859
|View full text |Cite
|
Sign up to set email alerts
|

Transition-Metal-Free Oxidative Homocoupling of Aryl, Alkenyl, and Alkynyl Grignard Reagents with TEMPO

Abstract: Oxidative homocoupling of aryl, alkenyl, and alkynyl Grignard reagents by using commercially available TEMPO as an organic oxidant is described. These coupling reactions occur highly efficiently without the presence of any transition metal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…To enable the Sonogashira cross coupling of the corresponding aryldibromide central units (structures 14–23 3239 in SI) at elevated temperatures, desilylation of 4-((trimethylsilyl)ethynyl)pyridine 40 with TBAF (1 M in THF) was performed in 1,4-dioxane (room temperature for 30 min). Since the light-sensitive 4-ethynylpyridine is not stable in air, the mixture was directly subjected to the aryldibromide in the presence of PdCl 2 (PhCN) 2 , CuI, t -Bu 3 P, and ( i -Pr) 2 NH, to give the target structures 1–10 in very good yields (Supplementary Note 1).…”
Section: Resultsmentioning
confidence: 99%
“…To enable the Sonogashira cross coupling of the corresponding aryldibromide central units (structures 14–23 3239 in SI) at elevated temperatures, desilylation of 4-((trimethylsilyl)ethynyl)pyridine 40 with TBAF (1 M in THF) was performed in 1,4-dioxane (room temperature for 30 min). Since the light-sensitive 4-ethynylpyridine is not stable in air, the mixture was directly subjected to the aryldibromide in the presence of PdCl 2 (PhCN) 2 , CuI, t -Bu 3 P, and ( i -Pr) 2 NH, to give the target structures 1–10 in very good yields (Supplementary Note 1).…”
Section: Resultsmentioning
confidence: 99%
“…TEMPO (2,2,6,6-tetramethyl-1-piperidinyloxy, 1.0 equiv) suppressed the coupling reaction of 1a and 2a but not to a complete extent, and 3aa was isolated in 45% yield (Figure b). Possibly, TEMPO was consumed as an oxidant for the PhMgBr homocoupling reaction . The results of light on/off experiments indicated that constant irradiation was required for product formation, while radical chain processes could not be excluded (Figure c) .…”
Section: Resultsmentioning
confidence: 99%
“…described transition‐metal‐free homocoupling of aryl, alkenyl, and alkynyl Grignard reagents by using the 2,2,6,6‐tetramethyl‐piperidine 1‐oxyl radical (TEMPO) as oxidant. The described reaction has produced high yields for homocoupling reactions for synthesis of polyfluorenes,poly(fluorenylenebutadiynylenes), and poly(fluorenylenebutadienylenes) . Another study presented by Cai et al.…”
Section: Introductionmentioning
confidence: 99%
“…The described reaction has produced high yields for homocoupling reactions for synthesis of polyfluorenes,poly(fluorenylenebutadiynylenes), and poly (fluorenylenebutadienylenes). [22][23][24][25] Another study presented by Cai et al described a method to synthesize of π-conjugated polymers containing 1,3-butadiene units by polycondensation using an organic base as the catalyst instead of toxic transition metal-based catalysts. [26] Their synthetic strategy was based on the reaction of α,β-unsaturated compounds containing γ-H with aldehyde compounds, where electron-withdrawing groups such as ester and nitrile are incorporated as side groups.…”
Section: Introductionmentioning
confidence: 99%